Ready and Able? Perceptions of Confidence and Teaching Support for First-Year Alternatively Certified Teachers. Issue 3 (3rd July 2022) - Keese, Jeffrey; Waxman, Hersh; Kelly, Larry J.
Abstract: To investigate the influence of preservice and in-service supports on teacher perceptions of their confidence to teach and of being supported, this study employed qualitative and quantitative approaches to analyze survey responses and interviews from teachers who received their preparation from a university-led alternative teacher certification program. Survey responses revealed that, prior to entering their classrooms for the first time, participants felt very confident in their ability to teach content, address student differences, manage student behavior, use instructional technology, and meet student needs. This confidence decreased upon entering their classrooms as full-time teaching interns, but survey responses indicated increasing confidence as those internships progressed. In interviews, teachers reported that while their preparation program was influential in shaping their early career experiences and future career plans, it was in-service supports and having a positive relationship with their school administrators which were more meaningful.